Diffusion tensor imaging in frontostriatal tracts is associated with executive functioning in very preterm children at 9 years of age - Kallankari Hanna; Saunavaara Virva; Parkkola Riitta; Haataja Leena; Hallman Mikko; Kaukola Tuula (SPRINGER, 2022)
Background Very preterm birth can disturb brain maturation and subject these high-risk children to neurocognitive difficulties later. Objective The aim of the study was to evaluate the impact of prematurity on microstructure of frontostriatal tracts in children with no severe neurologic impairment, and to study whether the diffusion tensor imaging metrics of frontostriatal tracts correlate to executive functioning.
Materials and methods The prospective cohort study comprised 54 very preterm children (mean gestational age 28.8 weeks) and 20 age- and gender-matched term children. None of the children had severe neurologic impairment. The children underwent diffusion tensor imaging and neuropsychological assessments at a mean age of 9 years. We measured quantitative diffusion tensor imaging metrics of frontostriatal tracts using probabilistic tractography. We also administered five subtests from the Developmental Neuropsychological Assessment, Second Edition, to evaluate executive functioning.
Results Very preterm children had significantly higher fractional anisotropy and axial diffusivity values (P<0.05, corrected for multiple comparison) in dorsolateral prefrontal caudate and ventrolateral prefrontal caudate tracts as compared to term-born children. We found negative correlations between the diffusion tensor imaging metrics of frontostriatal tracts and inhibition functions (P<0.05, corrected for multiple comparison) in very preterm children. Conclusion Prematurity has a long-term effect on frontostriatal white matter microstructure that might contribute to difficulties in executive functioning.